Recent advances in the diagnosis and treatment of vascular dementia (2012)
Introduction: vascular dementia is an acquired and persistent syndrome caused by vascular injuries in the central nervous system, altering the functions of intellect and cognition, which are essential for the biological, psychological and social balance on the individual. Objective: describe the recent advances in vascular dementia; diagnostic criteria, predisposing factors, epidemiology, neuropathology, and neurocognitive profile psychiatric and comprehensive therapeutic approach. Methods: updated review of the literature, using automated search of recent articles in journals indexed in biomedical database, during the months of March to May 2012. Results: we found 55 articles with updated information that consolidate the objectives of the review. Conclusions: vascular dementia has taken an important role on morbidity, especially in the geriatric population, as a result of the high prevalence of cerebrovascular diseases. Prevention, diagnosis, treatment and rehabilitation must be priorities in the clinical practice, given the importance of mental health in this population, which has been underestimated in Colombia. (MÉD.UIS. 2012;25(3):221-7).